Tendência temporal de acidentes com materiais perfurocortante entre profissionais de saúde de um hospital público: avaliação de um programa de prevenção. - Renan Sallazar Ferreira Pereira (2022)
Introduction: In Brazil, the highest rates of accidents with sharps occur in hospitals, with health professionals. As a strategy for dealing with accidents, the Ministry of Labor and Employment demanded the implementation of the Accident Prevention Program with Sharps (PPAMP) in hospitals. Objectives: 1. General: To analyze the temporal trend of the occurrence of accidents with sharps in a public hospital from the implementation of a prevention program; 2. Specifics: Article 1 – Describe the PPAMP implementation process in a public hospital; Article 2 – To analyze the temporal trend of accidents due to percutaneous exposure in a public hospital in Brazil between 2007 and 2019, according to sociodemographic and occupational characteristics of the health professionals; Article 3 – Compare the differences in the time series of accident rates with sharps before and after the implementation of the PPAMP in the hospital. Methods: This is a longitudinal study of a time series, with a documentary component. Study with three components: 1) Documentary – Article 1; 2) Time series analysis – Article 2; and 3) Interrupted historical series analysis – Article 3. The study was conducted in a public hospital. The population studied was composed of health professionals at risk of suffering an accident due to percutaneous exposure. The variables were collected by a researcher, in the database of the Specialized Service in Medicine and Occupational Safety, by filling out a semi-structured form. Article 1 – The variables of interest selected were: PPAMP implementation process and total number of occupational accidents with exposure to potentially contaminated biological materials. Data analysis was performed based on an exploratory, selective and analytical reading of the records, and the adequacy of the implementation of the PPAMP to the guidelines of Ordinance No. 1,748/2011 of the Ministry of Labor and Employment was verified. Article 2 – The selected variables of interest were: sociodemographic and professional data, accident profile, post-accident behavior data; number of accidents due to percutaneous exposure recorded, based on the diagnosis of occupational accidents with exposure to biological material Z20.9 in the 10th revision of the International Classification of Diseases, number of workers exposed to the risk of accidents due to percutaneous exposure. Descriptive analysis was performed by calculating absolute and relative frequencies. Monthly rates were averaged for each calendar year, (2007 to 2019). Prais-Winsten regression was used for trend analysis and calculation of annual percentage change, and the level of statistical significance was set at 5%. Article 3 – The variables of interest were: monthly incidence rate of occupational accidents due to percutaneous exposure (Outcome) and the preventive control measures adopted in the PPAMP (Interventions). Calculations of the predictions of the observations of the time series before the intervention were performed, to verify if the possible pattern existing in the series was changed after the PPAMP interventions. For the modeling, the packages Times Series Analysis and Functions for Time Series and Linear Models from RStudio were used. Methods and tools were used to display and analyze univariate time series forecasts, including exponential smoothing through state space models and automatic ARIMA modeling. Results: Article 1 – The program implementation process was completed in eight stages and complied with the directives of the Ordinance No. 1,748/2011. The program improved conventional control measures and led to the adoption of engineering measures. Article 2 – There was a downward trend in the rate of percutaneous injury among female workers (-0.012%; p=0.009), who had secondary education (-0.011%; p=0.035) and among all health professional categories (-0.010 %; p=0.019). An increasing trend (0.018%; p= 0.050) was observed among workers with ≥ 61 months of professional experience. Article 3 – The interrupted time series analysis showed a 17.81% reduction in the incidence rate after the implementation of the PPAMP. Conclusions: The PPAMP met all the guidelines required by the Ministry of Labor, serving as a model for other hospitals. The control measures adopted by the PPAMP were able to reduce the incidence of percutaneous accidents.